Zgodovina raziskovanja plazme - Južnič, Stanislav (Vakuumist, 1999)
Third part of the article describes scientific research in plasma physics in fusion reactors. We try to figure why the new field of plasma physics was formed so late among other fields of science and what benefit that retardationgives to it by putting plasma as a possible key for solving of the energetic crisis problem. We also try to descriibe some visions of the future of plasma.
Keywords: fizika plazme; reaktorji; fuzija; zgodovinski pregledi